Development and Evaluation of A Web-Based Course for Computing and Information Technology - Rasaratnam, Pawani (INTI Publishing House Sdn. Bhd., 2006)
Most educators in this country have heard about the World Wide Web that is growing at an exponential rate. Many have explored this resource, and some are now publishing their own materials for student access. Educational content on the Internet is rapidly increasing. More course materials are placed online to supplement classroom situations. Prior research found that this new web-based technology had not integrated sound pedagogical practices into the authoring process when developing new courses. One of the most widely acknowledged problems is the lack of knowledge of instructional development and delivery among educators. This research grew from the concern about the current status of instructional design in a college as well as the desire to help faculty implement Sound instruction on the web. The research justifies and describes instructional design principles that can be used to transform web material from simple informational resources to a powerful instructional medium. An overview of Instructional Design process is presented to guide us systematically to create the blue print or specification for the Web-based course. A sample Web-based course that includes all the important Instructional design principles is finally developed. The Web based course includes instructional goals, objectives, learning outcomes, instructional sequence, strategies as well as enrichment and remedial exercises. The Web-based course was reviewed and evaluated by two different groups of users- 25 students and two lecturers. A questionnaire was distributed at the end of the course to gather information related to the Web-based course. Instructional and technical aspects were evaluated. Interviews were carried out with the lecturers and randomly selected students. Pretest and posttest were conducted to assess the performance of students. Data collected from the feedback, interviews and assessments were analyzed using simple quantitative and qualitative statistics. Students’ scores in the pretest were compared with the posttest to find whether there was any improvement in performance. A t-distribution test was conducted to find if there was any significant difference. Interviews and feedback forms were used to find the acceptance of the Web-based course by the students and the lecturers. Guidelines to develop, implement and evaluate Web-based course are also proposed. These guidelines will help us develop a quality program to be delivered over the Web.